COMPARATIVE STUDY OF THE CHARACTERIZATION OF THE INTENSITY-DURATION-FREQUENCY (IDF) OF THE RAIN OF THE SAVE AND PARAKOU SYNOPTIC STATIONS IN THE REPUBLIC OF BENIN (WEST AFRICA) - VISSIN, EXPÉDIT WILFRID (My University, 2017)
The dimensioning of sanitation networks is today one of the major concerns of the scientific community, especially in the preservation of socio-economic, human and environmental challenges in the face of the high rainfall intensities of rare frequency. The purpose of this paper is to characterize rare-frequency rainfall in order to mitigate the damage caused by the high rainfall intensity on the socio-economic, human and environmental issues that they cause in the municipalities of Savè and Parakou. The methodological approach adopted for this study is based on the collection and processing of rainfall data related to rainfall intensities from the ASECNA pluviogram base over the period 1962 to 1999. The study was carried out by Log-normal law associated with the maximum likelihood method. The main results of this study result in three different forms of graphic and mathematical modeling of IDF curves. The evolution of these curves shows that the rain intensities and the rain heights have a differential behavior. Similarly, the heavy rain intensities which cause major damage have a duration of less than one hour with t = 5 min corresponding to 312 mm / h at Savéet 379.2 mm / h in Parakou. These results are intended for the design of the hydraulic and sanitation works of the municipalities of Savè and Parakou.
Keywords: Rain of rare frequency; Stakes; Intensity-Duration-Frequency; sizing